Improving musical skills for members of military band unit of Indonesian Army in administrative officer military area command IV Diponegoro Semarang - Sejati, Irfanda; Sunarto, Sunarto; Nugroho, Agustinus Arum Eka; Nugroho, Antonius Edi (Universitas Ahmad Dahlan, 2023)
Military music has a very significant role in every military event and government activity such as national ceremonies, important military ceremonies, and internal military activities. Military music also functions as a signal giver to high-ranking leaders such as the President and his staff, the Commander of the Indonesian National Armed Forces, Generals, and high commanders in the military. Since music is important within military units, a special unit called a military band unit was formed with the task of organizing military music activities and providing military music services to arouse a spirit of nationalism, professionalism, and patriotism for the personnel of the Indonesian National Armed Forces. The phenomenon that occurs in the military band unit is that not all personnel, especially the Army, have an academic background in music. Members from several units such as combat units can only play wind and percussion instruments but do not understand the basic techniques of music and playing musical instruments. This is because some members join the band unit due to the lack of personnel in the unit, and it is added to the high demands of members who are able to play music well. The solution to addressing this problem is to organize training to improve the musical skills of members of the military band unit, namely (1) reading and writing musical notation, (2) correct techniques in playing musical instruments, especially wind and percussion instruments, and (3) maintenance of musical instruments that are used daily.